Tooth colour shade matching: the effect of training on repeatability, and an investigation into a repeatable and reliable procedure - Gangadin, Megna (My University, 2020)
Visual shade analysis is most commonly used to determine shade, but can be enhanced by using instruments that measure colour according to the Commission Internationale de L’Eclairage (CIE) L*a*b* system. This study assessed whether visual shade matching ability was improved by a computerised training system; influenced by the use of instrumentation; and whether it changes over time. The inter-rater reliability of these methods was also evaluated. An additional aim was to devise a standardised shade taking protocol, and to test it for repeatability and reliability. Shade matching was assessed by asking two groups of participants to visually match, under controlled conditions, 9 unidentified tooth shades to the Vita 3D Master Shade Guide. In Part 1, the influence of age, gender, experience, training and time was examined for two groups of participants (n=75). One group received the computerised training system. Assessments were carried out on different occasions and two outcomes were measured: the number of incorrect tabs identified, and the deltaE of those tabs using the CIE2000 formula. An Acceptability Threshold of a deltaE of 2.7 was applied to the raw data. In Part 2, visual assessment alone; instrument assessment using a spectrophotometer alone; and any modifications of the visual selection as influenced by the instrument were compared. Inter-rater reliability of the visual and instrument assessments was also analysed. Results showed that age, gender, experience, training, and time had no significant effect on the participants’ abilities to correctly match the shade tabs. Visual assessment proved superior to instrumentation, but with poor inter-rater reliability. Continuous education and training would be required to improve the level and consistency of clinicians’ shade matching ability.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, School of Oral Health Sciences, University of Witwatersrand, Johannesburg, 2020